Síndrome de burnout y depresión en trabajadores de la Universidad Nacional del Centro del Perú - 2018 - Huachos Pacheco, Aníbal (2020)
This research begins with the question: What is the relationship between burnout syndrome and depression in workers of the National University of Central Peru, during the academic year 2018? The reason for this work was to establish the correlation between burnout syndrome and depression in workers of the National University of Central Peru, during the academic year 2018. The research was basic in nature. We used descriptive method allowing verifying the correlation between Burnout and depression. The descriptive research design was used corrections; the sampling was non-probability and intentional and to this end we have worked with 150 workers of the National University of Central Peru. The instruments that have been used for research are the inventory of Maslach and the Hamilton scale. In the study of the results obtained has been used the descriptive and inferential statistics. At the end showed the existence of a relationship between job burnout and depression.